The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3748/wjg.v21.i21.6491
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia infections among immunomodulated inflammatory bowel disease patients: A review

Abstract: Human nocardiosis, caused by Nocardia spp., an ubiquitous soil-borne bacteria, is a rare granulomatous disease close related to immune dysfunctions. Clinically can occur as an acute life-threatening disease, with lung, brain and skin being commonly affected. The infection was classically diagnosed in HIV infected persons, organ transplanted recipients and long term corticosteroid treated patients. Currently the widespread use of immunomodulators and immunossupressors in the treatment of inflammatory diseases c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 44 publications
0
37
0
3
Order By: Relevance
“…Specific risk factors have been reported for pneumonia due to Nocardia, Neisseria, Rhodococcus, and Q fever (Coxiella burnetii). Nocardiosis is associated with hematological and solid malignancies, high-dose steroid therapy, and TNFα antagonist therapy [25]. Risk factors for N. meningitidis infection are nasopharyngeal carriage and complement deficiencies [26].…”
Section: Bacterial Pneumoniamentioning
confidence: 99%
“…Specific risk factors have been reported for pneumonia due to Nocardia, Neisseria, Rhodococcus, and Q fever (Coxiella burnetii). Nocardiosis is associated with hematological and solid malignancies, high-dose steroid therapy, and TNFα antagonist therapy [25]. Risk factors for N. meningitidis infection are nasopharyngeal carriage and complement deficiencies [26].…”
Section: Bacterial Pneumoniamentioning
confidence: 99%
“…Newer immunosuppressive therapies such as monoclonal antibodies may also be a risk factor for infection and several cases of CNS nocardiosis have been reported in the setting of monoclonal antibodies. [2528] The concomitant use of multiple agents and corticosteroids in particular makes direct attribution of risk difficult. However, given the increasing number of individuals being placed on novel agents, this is an area which warrants further scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Nocardiosis is a rare and life-threatening opportunistic infection in immunocompromised hosts caused by ubiquitous soil-born, acid-resistant, Gram-positive bacteria. Originally usually diagnosed in HIV-positive patients, reports of Nocardia infection in IBD patients were summarized and presented by Abreu et al in 2015 [2]. The authors identified 11 cases of nocardiosis in patients with anti-TNF-α therapy, of which 7 patients had IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Nocardiosis and infection with atypical mycobacteria have been described in HIV-positive patients with substantial immunodeficiency. Only a few cases of nocardiosis in IBD patients have been reported [2]. We describe the first case of pulmonary co-infection with Nocardia spp.…”
Section: Introductionmentioning
confidence: 91%